Schimke immunoosseous dysplasia and management considerations for vascular risks. Issue 7 (30th April 2019) - Beleford, Daniah T.; Diab, Mohammad; Qubty, William F.; Malloy, Mary J.; Long, Roger K.; Shieh, Joseph T.
Abstract: Schimke immunoosseous dysplasia (SIOD) is a multisystemic condition characterized by early arteriosclerosis and progressive renal insufficiency, among other features. Many SIOD patients have severe, migraine‐like headaches, transient neurologic attacks, or cerebral ischemic events. Cerebral events could be exacerbated or precipitated by hypertension, and it is unclear how these are related to arteriosclerotic changes as dyslipidemia is also a feature of SIOD. The correlation between hypercholesterolemia and cardiovascular risk in SIOD is unclear. Also, the etiology and management of headaches is not well characterized. Here we report our clinical observations in the management of SIOD in a patient who was diagnosed in school age despite early signs and symptoms. We describe biallelic variants, including a previously unreported c.1931G>A (p.Arg644Gln) variant in SMARCAL1 . We specifically investigated whether migraine‐like headaches and progressive nephropathy may be related to blood pressure dysregulation. We found a correlation between tighter blood pressure regulation using ambulatory blood pressure monitoring and a subjective decrease in headache symptoms. We discuss blood pressure medication management in SIOD. We also characterize dyslipidemia relative to atherosclerosis risks and provide new management strategies to consider for optimizing care.